2019
DOI: 10.2147/ccid.s202884
|View full text |Cite
|
Sign up to set email alerts
|

<p>Keloid treatment: what about adjuvant radiotherapy?</p>

Abstract: Background: Keloids are debilitating fibrous skin proliferations with a high recurrence rate after surgical treatment. Postoperative radiotherapy (PORT) is a well-tolerated adjuvant treatment to reduce the risk of recurrence, but the optimal regimen for this combined treatment remains unknown. The aim of this study is to evaluate the efficacy of combining surgical excision and immediate PORT. Methods: We retrospectively reviewed the records of patients with keloid lesions tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…[ 14 ] Studies show that there is an increased activity of fibroblasts to a milder stimulus leading to excess production of the collagen. [ 2 ] This increased activity leads to hypertrophic scar or the keloid. For the same reason, recurrence in these conditions is a common feature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 14 ] Studies show that there is an increased activity of fibroblasts to a milder stimulus leading to excess production of the collagen. [ 2 ] This increased activity leads to hypertrophic scar or the keloid. For the same reason, recurrence in these conditions is a common feature.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] Surgical excision is effective in removing the existing tumor. [ 2 ] However, many studies have shown that surgical excision alone cannot prevent recurrence, and recurrence rate was as high as >50% at 1-year follow-up. [ 24 25 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations